Remarks about research challenges related to persistent sub-replacement fertility - Kotowska, Irena E. (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Sub-replacement fertility, observed in the 1970s and the 1980s in selected developed countries, has become a global phenomenon in the XXI century. In 2019 sub-replacement fertility was experienced in 93 countries and their populations amounted for nearly a half of the world population. The fertility developments and the synthesis of empirical research along with most known theoretical frameworks are presented. They are supplemented by comments about a paradigm shift in demographic research. This shift concerned ‘the transition in research from structures to processes, from macro to micro, from analysis to synthesis, and from certainty to uncertainty’ and the life course perspective as a leading research approach. This change contributed to progressing micro-level demographic research, especially as regards family related behaviours. The focus is on the international demographic research programmes: Family and Fertility Survey (FFS), carried out in the 1990s, and Generations and Gender Programme (GGP) initiated in 2000. New challenges in research on fertility, both in theoretical and empirical perspectives, refer inter alia to a increasing meaning of economic uncertainty and emergence of so-called generalised uncertainty. A new round of GGP, which started in 2020, responds to these challenges.